PENINGKATAN PRESTASI BELAJAR MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DALAM MATERI JUJUR - Ani Kartika (MGMP PAI Jawa Barat, 2022)
Honesty and not breaking promeses are the character of the Indonesian nation which is reflected in pancasila which is included in the values of Justice and Civilized Humanity. Honesty belongs to moral values and the basis of any comentable behavior. This honest character is important and must be possessed by all young generations of Indonesia, so that in the future the government will be held by honest people. The STAD Learning Model is one of the simplest and easiest types of cooperative learning to do. There are five components that must be considered in this learning model, namely class presentation, group study, quizzes, scores, and group awards. Data collection uses interview, observation and documentation techniques. The results showed that: 1) Learning planning has gone well learning planning oriented to the core competencies of the 2013 curriculum as stated in the Learning Implementation Plan (RPP); 2) The implementation of learning has gone well even though the results have not been optimal; 3) Evaluation of the implementation of the STAD learning model in honest material and keeping promises is good enough; 4) Supporting factors in the implementation of learning are professional teachers, young students, fun learning techniques, and adequate facilities and infrastructure.